2x+6=7x-2

Simple and best practice solution for 2x+6=7x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+6=7x-2 equation:


Simplifying
2x + 6 = 7x + -2

Reorder the terms:
6 + 2x = 7x + -2

Reorder the terms:
6 + 2x = -2 + 7x

Solving
6 + 2x = -2 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
6 + 2x + -7x = -2 + 7x + -7x

Combine like terms: 2x + -7x = -5x
6 + -5x = -2 + 7x + -7x

Combine like terms: 7x + -7x = 0
6 + -5x = -2 + 0
6 + -5x = -2

Add '-6' to each side of the equation.
6 + -6 + -5x = -2 + -6

Combine like terms: 6 + -6 = 0
0 + -5x = -2 + -6
-5x = -2 + -6

Combine like terms: -2 + -6 = -8
-5x = -8

Divide each side by '-5'.
x = 1.6

Simplifying
x = 1.6

See similar equations:

| 2(5x+4)=2(3m-10) | | 1/2q-1=6 | | 38-4x=5x+16 | | 7/8x+1/2=7/8 | | 34x+5=10 | | (6x+7/6)+(3/2)=-2x/7 | | -4-2x=12-8x | | x^4-18x^3+81x^2=0 | | 3(x+4)-4(x-3)= | | (6x+7/6)+(3/2)=-2 | | 2q-1=6 | | 4v^2-20v=0 | | 11-8x=139-36x | | 75-4x=14-8x | | x*3a=27 | | ((x-4)+1)/(x+1)=1/2 | | 5x^2+6x-12=2x | | 13b*17= | | 14n-21/7 | | 1/3x+5/6x=7/8 | | 8+(5-4x)-(1-x)=5x-2(x-3) | | 0.7/x=21 | | 7x+12=6+5x | | y=75+20x | | 8(c-2)-(c+3)= | | ((7x-1)/4)-1/3(2x-(1-x)/2)=19/3 | | 18(-x-2)-4(-9+3)=-14 | | 5m^2-9m+7m^2-2m= | | 17-x=12 | | 7a+7ab=2-3b | | 3.2n=n+7.8 | | 5x+(x+8)=-16-2x |

Equations solver categories